Scaling limit of virtual states of triatomic systems - Yamashita, M. T.; Frederico, T.; Delfino, A.; Tomio, Lauro [UNESP] (American Physical Society (APS), 2002)
For a system with three identical atoms, the dependence of the s-wave virtual state energy on the weakly bound dimer and trimer binding energies is calculated in the form of a universal scaling function. The scaling function is obtained from a renormalizable three-body model with a pairwise Dirac-[Formula Presented] interaction. The threshold condition for the appearance of the trimer virtual state was also discussed. 5555 2002 The American Physical Society.